Comparison of the Effectiveness of the Integrated Gottman and Emotion-Focused Therapy Model with the Imago Therapy Approach on Marital Adjustment and Love Styles in Married Students with Early Marriages - Khatibi, Jamileh; Haji Arbabi, Fatemeh; Fariborzi, Elham (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to compare the effectiveness of an integrated Gottman-EFCT model and Imago Therapy on marital adjustment and love styles in married students with early marriages. Methods and Materials: The study employed a quasi-experimental design with a pre-test, post-test, and control group. Forty-four participants were randomly assigned into two intervention groups: Integrated Gottman-EFCT (n = 15) and Imago Therapy (n = 14), along with a control group (n = 15). Each group underwent ten sessions of the respective therapy. Data were collected using the Dyadic Adjustment Scale (DAS) to assess marital adjustment and the Love Attitudes Scale (LAS) for love styles. ANOVA and t-tests were used to compare pre-test and post-test scores across groups. Findings: Significant improvements were observed in both intervention groups for marital adjustment and love styles. In the Gottman-EFCT group, the post-test mean for marital adjustment increased from 89.56 (SD = 9.45) to 110.65 (SD = 8.90) (t = 5.23, p = 0.001), while the Imago Therapy group showed a similar improvement from 88.45 (SD = 9.34) to 108.90 (SD = 9.15) (t = 5.10, p = 0.001). Love styles also significantly improved, with Eros increasing in the Gottman-EFCT group from 22.15 (SD = 3.50) to 28.75 (SD = 3.10) (t = 4.87, p = 0.001). The ANOVA results showed a significant between-group effect for marital adjustment (F = 72.21, p = 0.001, eta squared = 0.78). Conclusion: Both the Integrated Gottman-EFCT and Imago Therapy interventions were effective in improving marital adjustment and enhancing positive love styles in couples with early marriages. However, the integrated approach demonstrated a stronger effect across most variables, suggesting that a combined therapeutic approach may be more beneficial in addressing marital issues.